Adsorptive removal of alcohols from aqueous solutions by N-tertiary-butylacrylamide (NtBA) and acrylic acid co-polymer gel. (December 2019) - Chakraborty, Samayita; Bera, Rabin; Mandal, Arup; Dey, Ayan; Chakrabarty, Debabrata; Rene, Eldon R.; Lens, Piet N.L.
Abstract: A co-polymer gel of N-tert-butylacrylamide and acrylic acid was swelled in alcohols differing in its dipole moment and H-bonding interaction parameter so as to inspect the relative affinities of the gel towards alcohols. The gel swelled 900% in ethanol, 1200% in propanol and 750% in butanol. The extent of swelling can be used as a guide for preferential removal of particular alcohol from its mixture. Studies on adsorption isotherm using different isotherm equations helped in deciding the mechanism of adsorption of ethyl alcohol. The swelling and de-swelling kinetics of the gel in ethanol, propanol, and butanol (at low concentration of 5 g/l each) followed mostly Fickian type diffusions for the processes of absorption and desorption. The scope of repeated use of the gel for the alcohol recovery was investigated and every time approximately 98% alcohol could was found to be recovered. The honeycomb morphology of the gel was accountable for such swelling of the gel.